Childhood, abnormality, animality in the territory of the village. El pintadedos (1984) by Carlos Catania - Valeria Agustina Noguera (Estudios de Teoría Literaria)
The current literature takes up themes of nineteenth-century Argentine literature that seem to have been forgotten. This is the case of the territories imagined by these discourses that related corporalities to certain spaces, based on the idea of civilization and barbarism. In this line is located El pintadedos by Carlos Catania that places the narrative actions in the territory of the village San Carlos, inside the city of Santa Fe. In this literary zone there are various corporalities that are surrounded by the biopolitical mechanisms of the modern state but also those that exceed being in the place of the non-human. The village is the space in which the protagonist meets his animal past —and present—; but it is also the place where he feels part of a community that does not exist in the city in which he lives. This article will work on the ways in which the animality of the protagonist is manifested before the journey to the people, but it will also emphasize corporalities that inhabit this territory, through categories that are placed outside of the human, as that of childhood and abnormality.